A Symbiotic Relation Between Anti-Mullerian Hormone (AMH) and Vitamin D in Polycystic Ovary Syndrome (PCOS): A Meta-Analysis and Systematic Review - Patel, Kandarp J; Sheth, Haiya J; Mangrola, Nidhi Y; Patel, Neeti A (National Journal of Medical Research, 2025)
Background: The association of vitamin D levels with AMH and other hormones is still under exploration as mentioned in the existing literature. The capacity of vitamin D to regulate ovarian reserve, measured by the AMH level, is a subject of much discussion, especially in PCOS women. Thus, the present study was planned with a primary aim to assess and summarize the available evidence about the interrelationship between vitamin D and AMH levels in PCOS. Methods: A detailed literature search was done across various databases based on PRISMA guidelines till December 2024. Meta-analysis was done on 10 articles from the 37 articles selected for systematic review. Results: Serum AMH levels in PCOS subjects significantly decreased (SMD=-0.57; CI: -1.1 to 0.04; p=0.03) on vitamin D supplementation, while, it increased (SMD=-0.67; CI: 0.12 to 1.23; p=0.02) in non-PCOS women. Conclusion: This indicates a complex interplay of metabolic and hormonal parameters and makes vitamin D a potential factor for PCOS management.